Visual metaphors in food advertising: A cross-cultural study - Margariti, Kostoula; Boutsouki, Christina; Hatzithomas, Leonidas; Zotos, Yorgos (My University, 2019)
Even though, to date, numerous studies in food advertising have considered the use of visual metaphors, their impact on consumers' responses in diverse cultures has been only narrowly investigated. The present study scrutinizes the conditional indirect effect of visual metaphors on the moderated by culture attitude toward the ad and the resulting attitude toward the brand. Two 2 × 2 full factorial between-subjects experiments with two levels of visual metaphor (presence and absence) and two levels of culture (India and the USA) were used to test our hypotheses. Participants, 417 (207 Indian, 210 US) for the first experiment and 181 (82 Indian, 99 US) for the second experiment were divided in four treatment groups (one for each condition). Two versions of two print advertisements for a novel coffee and a novel ice-cream brand were the experimental stimuli in experiments 1 and 2 respectively. SPSS macro (PROCESS tool) was used for data analysis. Both experiments provided evidence in support of the proposed framework. Visual metaphors in high context cultures (India) seem to have a significantly more positive effect on attitude toward the ad and eventually on attitude toward the brand compared to low context environments (USA).
Keywords: Attitudes; Culture; Food Industry; Visual Metaphors